Glass heat transfer tester and test method thereof

By designing a small size and easy to handle glass heat transfer tester, using energy storage components and temperature measuring elements to closely fit the glass surface, the existing test methods have solved the problems of long measurement time and bulky equipment, and achieved fast and accurate measurement of glass heat transfer coefficient.

CN112432971BActive Publication Date: 2025-03-28LUOYANG LANDGLASS TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202011368993.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-11-30
Publication Date
2025-03-28
Estimated Expiration
2040-11-30

AI Technical Summary

Technical Problem

The existing glass thermal conductivity testing methods have problems such as long measurement time, strict ambient temperature requirements, bulky equipment and difficult to handle, and it is difficult to meet the testing needs of industrialized large-scale products.

Method used

A glass heat transfer tester is designed, using energy storage components and temperature measuring elements to closely fit the glass surface, and the lifting and lowering movement of the energy storage components is realized by driving the components, shielding the components from heat radiation, simplifying the testing steps and shortening the testing time.

Benefits of technology

It realizes the small size, light weight, beautiful appearance, easy to handle, short test time, suitable for large-scale testing, and can be used for heat transfer coefficient measurement of other flat plate solid materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112432971B_ABST
    Figure CN112432971B_ABST
Patent Text Reader

Abstract

The present invention relates to a glass heat transfer tester and a test method thereof, comprising an upper box body with a working port at the bottom; an energy storage component arranged in the upper box body for heating a glass plate during testing, a driving component for driving the energy storage component to reciprocate, and a shielding component for preventing the heat of the energy storage component from radiating downward; a lower box body arranged below the upper box body and spaced a set distance from the upper box body; a measuring component arranged in the lower box body for detecting temperature changes of the glass plate; and a connecting component arranged between the upper box body and the lower box body for connecting the upper box body and the lower box body. The glass heat transfer tester and the test method thereof disclosed in the present invention have a simple structure, accurate measurement, and a short measurement time. Even the thickest vacuum composite insulating glass can be measured within 30 minutes, and can be used for industrial mass testing. The present invention also includes a test method using the above-mentioned tester.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a heat conduction testing device, in particular to a glass heat conduction testing instrument and a testing method thereof. Background Art

[0002] Thermal conductivity U value is a physical quantity that measures the thermal conductivity of glass, which indicates the ability of glass to allow heat to pass through per unit area. At present, there are two main methods for testing thermal conductivity of glass: steady-state method and non-steady-state method. The steady-state method is to measure under the condition that heating and heat dissipation reach a balanced state and a stable temperature distribution is formed inside the sample to be tested. For details, please refer to JC / T Appendix A of 1079-2008 "Vacuum Glass" is a method for measuring the thermal insulation performance of vacuum glass. The steady-state method takes a long time to measure and has strict requirements on the ambient temperature, which makes it difficult to meet the testing needs of industrialized mass-produced products. The non-steady-state method refers to measuring under the condition that the temperature distribution inside the sample changes during the measurement process. For example, a glass thermal property tester (CN203798759U) uses constant temperature air as the heat source fluid to contact the glass surface, eliminating the influence of contact thermal resistance during glass thermal property testing. However, this solution requires heating with a constant temperature water bath to produce humid air of a certain temperature, and then drying it in an air drying chamber to obtain dry and constant temperature air. The tester is large and heavy, and cannot be easily carried. It is difficult to meet the application scenarios of enterprise sales personnel showing the thermal conductivity of products to customers when they go out to visit customers, or teachers showing the thermal conductivity of flat solid materials such as glass to students in class. Summary of the invention

[0003] In view of the problems existing in the prior art, the present invention provides a glass heat transfer tester and a test method thereof, which ensures that the energy storage block and the temperature measuring element are closely attached to the upper and lower surfaces of the glass, and the shielding component can effectively prevent the measuring component from absorbing heat and heating up, so as to accurately and reliably measure the heat transfer coefficient of the glass.

[0004] To achieve the above object, the technical solution of the present invention is as follows:

[0005] A glass heat transfer tester, characterized in that it comprises:

[0006] An upper box body with a working opening at the bottom;

[0007] Arranged in the upper box: an energy storage component for heating the glass plate during the test, a driving component for driving the energy storage component to reciprocate, and a shielding component for preventing the heat of the energy storage component from radiating downward;

[0008] A lower box body is arranged below the upper box body and is spaced a set distance from the upper box body;

[0009] A measuring component disposed in the lower box body and used to detect temperature changes of the glass plate;

[0010] A connecting component is arranged between the upper box body and the lower box body and is used to connect the upper box body and the lower box body.

[0011] Furthermore, the energy storage assembly includes: an energy storage block for heating the glass to be tested, a heating element arranged inside the energy storage assembly for heating the energy storage block, and a first temperature measuring element for measuring the temperature of the energy storage block.

[0012] Furthermore, the energy storage assembly also includes: a connecting plate for setting the energy storage block on the driving assembly, a guide plate for guiding the movement of the energy storage block, and an energy storage block shell for wrapping the energy storage block to avoid its heat energy loss, and the energy storage block shell is set on the connecting plate.

[0013] Furthermore, the lower surface of the energy storage block is a working surface, and the bottom of the energy storage block housing is provided with an opening through which the energy storage block can pass and contact the glass to be tested; the thermal conductivity of the energy storage block housing is less than 0.3W / m 2 ·K.

[0014] Furthermore, a pre-pressure device is provided between the connecting plate and the energy storage block housing, which can press the energy storage block tightly against the glass to be tested during testing.

[0015] Furthermore, the shielding assembly includes: a baffle plate for ensuring that heat of the energy storage block is not dissipated during heating, and a counterweight block, a rotating shaft and a baffle shaft for driving the baffle plate to move.

[0016] Furthermore, a display component for controlling the measurement process and displaying the measurement results is also provided on the outer side of the upper box.

[0017] Furthermore, the connecting component is one or more hollow cylinders.

[0018] Furthermore, the measuring assembly includes: a second temperature measuring element for measuring the temperature of the glass plate to be measured; a substrate for fixing the second temperature measuring element on the top of the lower box; a guide shaft for fixing the second temperature measuring element on the substrate and guiding its movement; and a spring sleeved on the guide shaft for driving the second temperature measuring element to reciprocate along the guide shaft.

[0019] Using the measurement method of the glass heat transfer tester mentioned above, the initial temperature of the lower surface of the glass is set to T 1 , after the set time t s The temperature of the lower surface of the glass after heat transfer is T 2 , temperature difference ΔT=T 2 -T 1 , characterized in that it comprises the following steps:

[0020] Step 1: Place the glass to be tested in the glass heat transfer tester between the upper and lower boxes, and record the initial temperature T measured by the measuring component attached to the lower surface of the glass. 1 ;

[0021] Step 2: Turn on the heating element in the energy storage assembly to heat the energy storage block, and stop heating after the temperature of the energy storage block rises to a set value and remains constant;

[0022] Step 3: The energy storage component descends and fits tightly against the upper surface of the glass to be tested;

[0023] Step 4: After the set time t s After the heat transfer, record the temperature value T of the lower surface of the glass measured by the measuring component attached to the lower surface of the glass 2 ;

[0024] Step 5: Substitute ΔT into the formula The U value of the glass to be tested can be obtained;

[0025] Step 6: After the measurement is completed, the energy storage component returns to a predetermined position, that is, the starting position of the reciprocating motion of the energy storage component.

[0026] Furthermore, the method further comprises step 7: repeating steps 1 to 6 to achieve continuous testing of the U value of the glass to be tested.

[0027] Furthermore, let the basic sample measurement time be t 0 The thickness increment of the glass to be tested compared to the base sample is A 1 The thickness increment of the cavity of the glass to be tested compared to the base sample is A. 2 , the glass thickness increment parameter is K 1 ; The cavity thickness increment parameter is K 2 , the set time t s =(A 1 ×K 1 +A 2 ×K 2 )+t 0 ; Among them, the basic sample measurement time t 0 Between 200-500 seconds; K 1 With K 2 The value range of K is between 20 and 45. 1 ≠K 2 .

[0028] Furthermore, the set value in step 2 is 80-130°C.

[0029] The present invention discloses a glass heat transfer tester and a test method thereof, wherein a high heat-conductivity energy storage component is used on one side of the glass to be tested to heat it, and a temperature measuring element is used on the other side of the glass to be tested to measure its temperature, which greatly simplifies the test steps, shortens the test time, and has the following technical effects:

[0030] 1. The glass heat transfer tester has the characteristics of small size, light weight, beautiful appearance, easy to carry, etc. It can be used in laboratories, workshops, offices, classrooms and other places;

[0031] 2. Both the energy storage component and the measuring component are equipped with springs to ensure that the energy storage block and the second temperature measuring element fit tightly against the upper and lower surfaces of the glass, making the measurement results more accurate and reliable;

[0032] 3. The driving component uses a driving motor installed on the top of the linear slide to drive the energy storage component to rise and fall. The displacement of the energy storage component can be accurately controlled according to the thickness of the glass to be measured, ensuring that the spring pressure is constant and reliable during each measurement.

[0033] 4. The baffle of the shielding component set inside the upper box is in a normally closed state. It will be opened only when the glass heat transfer coefficient is tested. At this time, the measuring component of the lower box has been covered by the glass to be tested, which is conducive to maintaining the ambient temperature of the measuring component and avoiding the measurement result deviation caused by the radiation of the energy storage block. The baffle of the shielding component adopts a non-powered opening and closing structure, which is simple, light and highly reliable;

[0034] 5. The test takes a short time. Even the thickest vacuum composite insulating glass can be measured within 30 minutes, which can be used for industrial mass testing.

[0035] 6. This tester can also be used to measure the heat transfer coefficient of other flat solid materials that can withstand the temperature of the energy storage block. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a schematic diagram of the structure of the glass heat transfer tester of the present invention;

[0037] Figure 2 Schematic diagram of the internal structure of the glass heat transfer tester of the present invention (right view);

[0038] Figure 3 This is a schematic diagram of the internal structure of the glass heat transfer tester of the present invention (front view);

[0039] Figure 4 for Figure 2 The enlarged image at point I in the middle;

[0040] Figure 5 for Figure 2 Enlarged view of II in the middle;

[0041] Figure 6 for Figure 3 Enlarged view of point III in the middle. DETAILED DESCRIPTION

[0042] like Figure 1 As shown, the glass heat transfer tester disclosed in the present invention comprises an upper box body 1 and a lower box body 2, and the two boxes are connected and fixed to each other through a connecting assembly 3. The upper box body 1 and the lower box body 2 are arranged at an interval, and there is a set distance between the two, so that the glass to be tested (not shown in the figure) can be inserted therein.

[0043] like Figure 1-3 As shown, a driving component, an energy storage component 5 and a shielding component 7 are installed inside the upper box body 1. The upper box body 1 is a closed box body with a working port at the bottom, and a display component 11 with the function of operation input and displaying measurement results is also arranged on the outside. The lower box body 2 is a closed box body with an opening at the top, and a measuring component 6 is arranged inside it, and a leveling support 21 for adjusting the level of the instrument is installed at the bottom. The connecting component 3 is preferably one or more hollow cylinders, which, in addition to being used to connect the upper box body 1 and the lower box body 2, also has the function of threading cables to supply power to various components in the upper box body 1 and the lower box body 2, so that the appearance of the equipment is more beautiful and the cables are effectively protected to avoid breakage and leakage during the test. The driving component is preferably a linear slide 4 provided with a driving motor, and the energy storage component 5 can be raised and lowered along the linear slide 4. Of course, other driving devices can also be selected according to needs.

[0044] like Figure 2-4 As shown, the energy storage assembly 5 includes a connecting plate 51 , a guide plate 52 , an energy storage block 53 , a heating rod 54 , a first temperature measuring element 55 , an energy storage block housing 56 and a pre-pressure device 57 .

[0045] like Figure 2-4 As shown, the connecting plate 51 is used to fix the energy storage assembly 5 as a whole on the linear slide 4. The specific connection method is that the connecting plate 51 is connected to the energy storage block housing 55, and the guide plate 52 is fixed on the energy storage block housing 56, and rises and falls with the energy storage block 53; the guide plate 52 is used to guide the reciprocating motion of the energy storage block 53. In addition, after the energy storage block 53 descends, the guide plate 52 plays a role in keeping the baffle 71 in an open state, so as to prevent the baffle 71 from turning back after the energy storage block 53 descends, and then being stuck when the energy storage block 53 rises again. The pre-pressure device 57 is used to provide pre-pressure for the energy storage block 53, so that it can fit tightly with the upper surface of the glass to be tested during the test, and to avoid damage to the glass to be tested caused by the excessive descending distance of the energy storage block 53. The pre-pressure device 57 is preferably one or more springs on the bolts between the connecting plate 51 and the energy storage block housing 55. Of course, other elastic devices that can provide pre-pressure can also be selected.

[0046] like Figure 2-4 As shown, the energy storage block 53 is made of a material with a high thermal conductivity, and the value range of the thermal conductivity is 200w / (m 2 ·k) or more, preferably copper (thermal conductivity 386.4w / (m 2 ·k)), the lower surface of the energy storage block 53 is a working surface, which is used to contact with the glass plate to be tested and heat the glass plate to be tested. One or more heating rods 54 and a first temperature measuring element 55 are installed inside the energy storage block 53. The heating rod 54 is used to heat the energy storage block 53, and the first temperature measuring element 55 is used to measure the temperature of the energy storage block 53, and the output power of the heating rod 54 is adjusted according to the temperature of the energy storage block 53, so that the temperature of the energy storage block 53 can quickly reach and maintain the set value. The energy storage block shell 56 is sleeved on the outside of the energy storage block 53, and is used to keep the energy storage block 53 warm. The thermal conductivity of the material used for the energy storage block shell 56 is less than 0.3W / m 2 K, since the lower surface of the energy storage block 53 is the working surface, the rest of the energy storage block 53 except the lower surface is covered by the energy storage block housing 56 to reduce the energy loss during operation and ensure that the measurement result is accurate and reliable. Preferably, in order to better maintain the temperature of the energy storage block 53, a heat insulating material can be filled between the energy storage block 53 and the energy storage block housing 56.

[0047] like Figure 2-4 As shown, the linear slide 4 is fixedly arranged in the upper box body 1. The driving motor at the top of the linear slide 4 is used to drive the energy storage component 5 to perform lifting movement, and the energy storage component 5 is fixedly connected to the linear slide 4 through the connecting plate 51 therein. When the glass to be tested is tested, the energy storage component 5 can be driven by the driving motor at the top of the linear slide 4 to descend, and pass through the working port 12 to fit with the upper surface of the glass to be tested, and the energy storage component 5 is pressed down to a certain displacement in the form of the pre-pressure force of the pre-pressure device 57. Under the action of the pre-pressure device 57, the lower surface of the energy storage block 53 is always tightly fitted with the upper surface of the glass to be tested during the test, ensuring that the error of the test result is small. After the test is completed, the energy storage component 5 returns to the predetermined position driven by the driving motor at the top of the linear slide 4, that is, the starting position of the reciprocating motion of the energy storage component 5. Preferably, this can be achieved by setting a limit device at the starting position of the lifting and lowering of the upper part of the linear slide 4, such as an origin switch.

[0048] When the energy storage block 53 descends to the surface of the glass to be tested, it should protrude 1-2 mm beyond the bottom of the energy storage block shell 56, so that the lower surface of the energy storage block 53 can be better attached to the upper surface of the glass to be tested and the energy storage block shell 56 can be prevented from pressing onto the glass to be tested. Moreover, since the heat insulation material between the energy storage block 53 and the energy storage block shell 56 usually has a certain elasticity, after the energy storage block 53 is pressed onto the glass to be tested, the heat loss around the protruding part of the energy storage block 53 is negligible due to the elastic action of the heat insulation material.

[0049] like Figure 3 and Figure 6 As shown, the shielding assembly 7 is arranged between the energy storage assembly 5 and the measuring assembly 6, preferably, arranged in the upper box body, and located on the descending path of the energy storage assembly 5. The shielding assembly 7 includes a baffle 71, a counterweight block 72, a rotating shaft 73 and a blocking shaft 74. A steel pipe is welded on the baffle 71, which is sleeved on the rotating shaft 73, and the structure is similar to a hinge. After the test is completed, the energy storage assembly 5 rises, and the baffle 71 rotates counterclockwise around the rotating shaft 73 to a horizontal position under the action of the counterweight block 72, and is blocked by the blocking shaft 74. At this time, the baffle 71 is closed, and the energy storage block 53 is shielded in the upper box body 1, which can prevent heat from radiating downward.

[0050] like Figure 2 and Figure 5 As shown, the measuring assembly 6 is arranged in the lower box 2, preferably, at the top. The measuring assembly 6 comprises a substrate 61, a guide shaft 62, a spring 63 and a second temperature measuring element 64. The substrate 61 is fixedly arranged on the upper surface of the lower box, the spring 63 is sleeved on the guide shaft 62, the guide shaft 62 passes through the substrate 61, and the second temperature measuring element 64 is arranged on the top of the guide shaft 62. In the free state, the second temperature measuring element 64 should be higher than the upper surface of the substrate 61 and higher than the upper surface of the lower box 2. When measuring, the glass to be measured needs to be placed flat on the measuring assembly 6. At this time, the second temperature measuring element 64 is pressed to the same height as the substrate 61 under the action of the self-weight of the glass to be measured, and under the action of the spring 63, the second temperature measuring element 64 is always tightly fitted with the lower surface of the glass to be measured during the measurement process, and the temperature of the lower surface of the glass can be accurately measured, and dynamic measurement data can be recorded. After the measurement, the second temperature measuring element 64 is reset under the action of the spring 63.

[0051] Since the types and thicknesses of the glass to be tested vary greatly, the time to complete the test also varies. For example, the test for common specifications of vacuum glass can be completed within 8 minutes; while for vacuum composite insulating glass, the test can be completed within 30 minutes.

[0052] The test principle of the glass heat transfer tester of the present invention is: directly measure the temperature difference change in the center of the glass to be tested, and then convert the thermal insulation performance of the glass through a formula. Glass with different heat transfer coefficients will have different surface temperature difference changes after the heat flow transfer of the energy storage block. The smaller the heat transfer coefficient, the smaller the temperature difference on the glass surface. The specific relationship is obtained by the following steps:

[0053] Before starting the test, the surface of the glass to be tested needs to be cleaned in advance to prevent dust on the surface of the glass from affecting the test results. The glass to be tested is placed on the heat transfer tester between the upper and lower boxes. The initial temperature measured by the measuring component attached to the lower surface of the glass is recorded as T. 1; Then, the heating rod 54 is turned on. When the temperature of the energy storage block 53 rises to the set value and remains constant, the heating is stopped. At this time, the heat value stored in the energy storage block 53 is a constant value; the energy storage assembly 5 descends and fits tightly with the upper surface of the glass to be tested. The energy storage block 53 transfers heat to the glass to be tested; after the set time t s After the heat transfer, the temperature value measured by the measuring component 6 attached to the lower surface of the glass to be measured is set as T 2 , calculate the temperature difference ΔT, where ΔT = T 2 -T 1 , the temperature difference ΔT is brought into the calculation formula of the heat transfer coefficient to obtain the U value of the glass to be tested; after the measurement, the energy storage component 5 returns to the predetermined position, that is, the starting position of the upper lifting of the linear slide 4, and then the heating rod 54 starts to work to supplement the temperature of the energy storage block 53 until the temperature of the energy storage block 53 is maintained at the set value again, and then the next measurement can be started. The glass heat transfer tester of the present invention is set to a time t s The heat transfer rate of the glass is measured by the temperature rise of the lower surface of the glass to be tested. The heat transfer coefficient of the glass to be tested is accurately displayed on the display screen in the display component through calculation. If the same sample needs to be measured multiple times to get the average value, the glass to be tested needs to be cooled in the test environment to the test environment temperature before retesting.

[0054] For composite glass, as the glass thickness increases and the cavity thickness increases, the set time t in the above steps is calculated according to the following formula: s , that is, T 2 With T 1 The measurement interval t s =(A 1 ×K 1 +A 2 ×K 2 )+t 0

[0055] Among them, A 1 A is the thickness increment of the glass to be tested compared to the base sample. 2 The thickness increment of the cavity of the glass to be tested compared to the base sample;

[0056] K 1 is the glass thickness increment parameter, K 2 is the cavity thickness increment parameter, K 1 With K 2 The value range of K is between 20 and 45. 1 ≠K 2 ;

[0057] t 0 The measurement time for the basic sample;

[0058] After preliminary experiments, it was found that the basic sample measurement time t 0 Too short, basic sample measurement time t 0 If the temperature of the energy storage block 53 is too low, the temperature difference ΔT of the basic sample will be relatively small. The comparison result of the thermal insulation performance of the glass samples produced in the same batch is not obvious, which is not conducive to screening out the glass with poor thermal insulation performance in the same batch. 0 Preferably, it is between 200-500 seconds; the temperature setting value of the energy storage block 53 is not less than 80°C, preferably 80-130°C.

[0059] The above setting time t s The calculation formula is applicable to the measurement time calculation of vacuum glass and insulating glass composite glass components; when testing the heat transfer coefficient of insulating glass, take the basic sample measurement time t 0 =0; When testing single-layer glass or sheets of other materials, it is necessary to set the appropriate energy storage block measurement temperature and measurement time according to the material.

[0060] The above heat transfer coefficient calculation formula is established by the following steps:

[0061] 1. Use this tester to measure the temperature difference ΔT on the lower surface of the glass;

[0062] 2. Measure the U value of the glass system by the steady-state heat flow method;

[0063] 3. Repeat the above steps with different glasses to measure the temperature difference ΔT of the glasses respectively. 1 , ΔT 2 , ΔT 3 ..., the U value of glass 1 , U 2 , U 3 ..., establish a database on glass temperature difference and U value;

[0064] 4. Fit the relationship between U and ΔT. The formula is as follows:

[0065] Note: The values ​​of a, b, and c are related to the structure and thickness of the glass. The specific curve fitting process belongs to the prior art and will not be described here.

[0066] Taking composite vacuum glass as an example, the test results obtained by this tester are compared with the test results of the standard test method for determining steady-state thermal conductivity characteristics using a heat flow meter in ASTM C518-2010 as follows:

[0067] Table 1 shows the U-value test results of vacuum glass and vacuum composite insulating glass. It can be seen from Table 1 that the measuring method and measuring device disclosed in the present invention can measure the U-value of vacuum glass and vacuum composite insulating glass in a short time with small error and strong practicality.

[0068] Table 1

[0069]

[0070]

[0071]

[0072] Note: In Table 1, t represents tempered glass, l represents Low-E glass, v represents vacuum layer, A represents air layer, and the coefficients before t, v, and A represent thickness in millimeters. The glass configuration of the basic sample in Table 1 is 4t+0.3v+4tl, which means that the upper substrate of the vacuum glass is 4mm thick tempered glass, the lower substrate is 4mm thick Low-E tempered glass, and the middle is a 0.3mm thick vacuum layer.

Claims

1. A glass heat transfer tester, characterized in that: include: An upper box body with a working opening at the bottom; Arranged in the upper box: an energy storage component for heating the glass plate during the test, a driving component for driving the energy storage component to reciprocate, and a shielding component for preventing the heat of the energy storage component from radiating downward; A lower box body is arranged below the upper box body and is spaced a set distance from the upper box body; A measuring component disposed in the lower box body and used to detect the temperature change of the glass plate, the measuring component comprising: a second temperature measuring element used to measure the temperature of the glass plate to be measured; A connecting assembly disposed between the upper box and the lower box and used to connect the upper box and the lower box; The energy storage assembly comprises: an energy storage block for heating the glass to be tested, a heating element arranged inside the energy storage assembly for heating the energy storage block, and a first temperature measuring element for measuring the temperature of the energy storage block; The energy storage assembly further comprises: a connecting plate for setting the energy storage block on the driving assembly, a guide plate for guiding the movement of the energy storage block, and an energy storage block shell for wrapping the energy storage block to avoid heat loss thereof, wherein the energy storage block shell is arranged on the connecting plate; The shielding assembly comprises: a baffle plate for ensuring that the heat of the energy storage block is not lost during heating, and a counterweight block, a rotating shaft and a blocking shaft for driving the movement of the baffle plate; the shielding assembly is arranged between the energy storage assembly and the measuring assembly, and is located on the descending path of the energy storage assembly; the baffle plate is in a normally closed state, and when the glass heat transfer coefficient is tested, the baffle plate is opened, and after the test is finished, the energy storage assembly rises, and under the action of the counterweight block, the baffle plate is blocked by the blocking shaft when it rotates counterclockwise around the rotating shaft to a horizontal position, and the baffle plate is closed to block the heat from radiating downward; When testing: Assume that the initial temperature of the lower surface of the glass is T1, and the temperature of the lower surface of the glass after the set time ts of heat transfer is T2. The temperature difference ΔT=T2-T1 is characterized in that it includes the following steps: Step 1: Place the glass to be tested in the glass heat transfer tester between the upper and lower boxes, and record the initial temperature T1 measured by the measuring component attached to the lower surface of the glass; Step 2: Turn on the heating element in the energy storage assembly to heat the energy storage block, and stop heating after the temperature of the energy storage block rises to a set value and remains constant; Step 3: The energy storage component descends and fits tightly against the upper surface of the glass to be tested; Step 4: After the set time ts of heat transfer, record the temperature value T2 of the lower surface of the glass measured by the measuring component attached to the lower surface of the glass; Step 5: Substitute ΔT into the formula The U value of the glass to be tested can be obtained, where U is the thermal conductivity, and a, b, and c are all constants; Step 6: After the measurement is completed, the energy storage component returns to a predetermined position, that is, the starting position of the reciprocating motion of the energy storage component.

2. The glass heat transfer tester according to claim 1, characterized in that: The lower surface of the energy storage block is a working surface, and the bottom of the energy storage block housing is provided with an opening through which the energy storage block can pass and contact the glass to be tested; the thermal conductivity of the energy storage block housing is less than 0.3W / m 2 ·K.

3. The glass heat transfer tester according to claim 1, characterized in that: A pre-pressure device is also provided between the connecting plate and the energy storage block housing, which can press the energy storage block tightly against the glass to be tested during testing.

4. The glass heat transfer tester according to claim 1, characterized in that: A display component for controlling the measurement process and displaying the measurement results is also arranged on the outer side of the upper box.

5. The glass heat transfer tester according to claim 1, characterized in that: The connecting component is one or more hollow cylinders.

6. The glass heat transfer tester according to claim 1, characterized in that: The measuring assembly also includes: a base plate for fixing the second temperature measuring element on the top of the lower box; a guide shaft for fixing the second temperature measuring element on the base plate and guiding its movement; and a spring sleeved on the guide shaft for driving the second temperature measuring element to reciprocate along the guide shaft.

7. The tester according to claim 1, characterized in that: The method further comprises step 7: repeating steps 1 to 6 to achieve continuous testing of the U value of the glass to be tested.

8. The tester according to claim 1, wherein the basic sample measurement time is t0, the glass thickness increment of the glass to be tested compared with the basic sample is A1, the cavity thickness increment of the glass to be tested compared with the basic sample is A2, the glass thickness increment parameter is K1, and the cavity thickness increment parameter is K2, wherein: The setting time t s =(A1×K1+A2×K2)+t0; The basic sample measurement time t0 is between 200 and 500 seconds; the value range of K1 and K2 is between 20 and 45, and K1≠K2.

9. The tester according to claim 1, characterized in that: The set value in step 2 is 80-130°C.

Citation Information

Patent Citations

  • Glass thermophysical property tester

    CN203798759U

  • Device and method for rapidly detecting heat transfer coefficient of glass based on unsteady-state heat transfer technology

    CN105891257A

  • Coefficient of heat conductivity tester

    CN206990483U

  • Glass heat transfer tester

    CN213779944U